Characterization of microcrystalline cellulose isolated through mechanochemical method - Norhafzan, Junadi; Beg, M. D. H.; R. M., Yunus; Ridzuan, Ramli; Zianor Azrina, Z. A.; Alam, A. K. M. Moshiul (IJFTR CSIR-NISCAIR, 2019)
Mechanochemical process, which involves simultaneous ultrasound and alkali treatment, has been used to isolatemicrocrystalline cellulose (MCC) from raw oil palm empty fruit bunch (REFB) fibre. Three steps have been used to preparethe MCC, namely removal of lignin, removal of hemicellulose and finally production of MCC. The crystallinity index inMCC is found to be 81% which is 54% higher than that of REFB and 45% higher than that of cellulose. Besidescrystallinity, the crystal size (28.03Å) of MCC is also enhanced noticeably by 53% as compared to the REFB and 28% ascompared to cellulose. The degradation temperature, and the residue content reveal the excellent thermal stability of MCCextracted through this mechanochemical technique.